A nationwide survey on the management of neonatal respiratory distress syndrome: insights from the MUNICH survey in 394 Chinese hospitals - Long Chen; Yong Ji; Rong Ju; Jiang-Qin Liu; Ling Liu; Jingyun Shi; Hui Wu; Lili Wang; Falin Xu; Chuanzhong Yang; Huayan Zhang; Yuan Shi; et al. (BMC, 2024)
Abstract Background At present, preterm infants with respiratory distress syndrome (RDS) in China present higher mortality and morbidity rates than those in high-income countries. The aim of this nationwide survey was to assess the clinical management of RDS in China. Methods A nationwide cross-sectional survey to assess adherence to RDS management recommendations was performed. One neonatologist per hospital was randomly selected. The primary outcome was the key care of RDS management. Results Among the 394 participating hospitals, 88·3% were birthing centres. The number of doctors and nurses per bed were 0·27 and 0·72, respectively. Antenatal corticosteroids (any dose) were administered to 90% of the women at risk of preterm birth at < 34 weeks of gestation (90·0% inborn vs. 50·0% outborn, p < 0·001). The median fraction of inspired oxygen (FiO2) for initial resuscitation was 0·30 for babies born at ≤ 32 weeks of gestation and 0·25 for those born at > 32 weeks. T-piece resuscitators were available in 77·8% of delivery rooms (DRs) (tertiary hospitals: 82·5% vs. secondary hospitals: 63·0%, p < 0·001). Surfactant was used in 51·6% of the DRs. Less invasive surfactant administration (LISA) was used in 49·7% of the hospitals (tertiary hospitals: 55·3% vs. secondary hospitals: 31·5%, p < 0·001). Primary non-invasive ventilation was initiated in approximately 80·0% of the patients. High-frequency oscillation ventilation was primarily reserved for rescue after conventional mechanical ventilation (MV) failure. Caffeine was routinely used during MV in 59·1% of the hospitals. Bedside lung ultrasonography was performed in 54·3% of the health facilities (tertiary hospitals: 61·6% vs. secondary hospitals: 30·4%, p < 0·001). Qualified breast milk banks and Family Integrated Care (FICare) were present in 30·2% and 63·7% of the hospitals, respectively. Conclusions Significant disparities in resource availability and guidelines adherence were evident across hospitals. Future strategies should address DR facilities and medication access, technical training, staff allocation, and ancillary facility development for a better management of RDS patients in China.